Desafíos de la educación superior. Consideraciones sobre el Ecuador - Ruiz Gutiérrez, Lourdes (2018)
The present work takes as a target to analyze the Ecuadorian higher education system contemporary from a methodology based on methods of information, analysis and synthesis. The used methods are based on a historical critique of the schools of world thought and its influence in the Latin-American reality; from, documentary search of bibliographical sources and a case study of the Ecuadorian university. There concludes with the exposition of a model education -learning based the employment of current legal instruments and the diagnosis of the problems or critical nodes of the system of higher education in the Ecuador and conclusions that can reach port to the improving of the system of higher education in our country.